Tacrolimus exposure during the three-month period following allogeneic stem cell transplantation predicts overall survival - Zavrelova, Alzbeta; Zibridova, Katerina; Radocha, Jakub; Cermakova, Eva; Rozsivalova, Petra; Zak, Pavel; Visek, Benjamin; Lanska, Miriam; Stevkova, Jana; Merdita, Sara; Slanar, Ondrej; Sima, Martin (Frontiers in Pharmacology, 2025)
ObjectivesThe objective of this study was to investigate the relationship between both short-term and long-term tacrolimus exposure and overall survival after allogeneic stem cell transplantation and to propose individualized tacrolimus dosing based on the population pharmacokinetic model.Study designTacrolimus exposure during the first 3 months of therapy after transplantation was calculated using therapeutic drug monitoring data from all patients who underwent allogeneic stem cell transplantation from 2016 to 2018. The optimal upper level was determined using ROC analysis, and the impact of cutoff tacrolimus exposure values on overall survival of patients was assessed together with other transplant variables using multivariate analysis. The population pharmacokinetic model was developed using a nonlinear mixed-effects modeling method, and the optimal tacrolimus dose was proposed.ResultsA total of 86 patients were included in the outcome analyses. Except for the disease risk category, age ≥55 years, and female-to-male donor, tacrolimus exposures of the area under the curve of trough concentrations (AUCtc) ≥ 222 ng h/mL, ≥258 ng h/mL, and ≥160 ng h/mL during the whole three-month period, second month, and third month of therapy, respectively, were also found to be statistically significant for overall survival in univariate analysis. These AUCtc values were independent variables for overall survival in multivariate analysis, with RR of 3.01 (P = 0.0056), 3.22 (P = 0.0058), and 2.93 (P = 0.0184) for the whole three-month period, second month, and third month of therapy, respectively. The disease risk category (RR 7.11; P < 0.0001), age (RR 2.45; P = 0.0214), and non-myeloablative conditioning (RR 3.39; P = 0.0014) were also significant factors influencing survival in multivariate analysis. Tacrolimus volume of distribution was 127.1 L and was not affected by any of the tested covariates, whereas clearance decreased with age according to the equation CL=7.94×e−0.0085×age and was reduced by 23% in patients who underwent repeat transplantation.ConclusionExcept for the disease risk category, age, and non-myeloablative conditioning, exposure to tacrolimus is an independent predictor of overall survival and should not exceed trough levels of 10.7 ng/mL during the second month and 6.8 ng/mL during third month after transplantation. In order to reach this target, nomogram for estimation of the maximal initial tacrolimus daily dose was developed based on the population pharmacokinetic model.